Trapping of gold nanoparticle and polystyrene beads by dynamic optical tweezers - Abd. Aziz, Muhammad Safwan (Penerbit UTM Press, 2015)
Gold nanoparticles and polystyrene beads are very important to use in advanced nanoscopic optical trapping techniques to probe any biological system of interest. Multiple trapping of these particles with different diameters can be performed by an optical tweezers system employing dark soliton controlled by Gaussian pulse within a particular configuration of microring resonators. By controlling some parameters and input power of the system, dynamics of the tweezers can be tuned. Radiation pressure acting on the particles including gradient and scattering forces were theoretically measured as a function of normalized position from the center of the laser beam. In this work, the highest output signal in the form of potential well is recorded at 112.80 W corresponding to 1.6 pm wavelength. Sizes of the tweezers are found within the range of 20 nm and the highest value of the optical force is recorded at 895.70 pN. We have demonstrated that the gradient force component is dominant over particle size within Rayleigh regime, thus a good agreement with theory is found.